Economic, social and cultural human rights in the context of preventing the spread of COVID-19 in Ukraine (Law and Safety, 2020)
Anti-epidemic measures introduced in Ukraine to prevent the spread of COVID-19 include significant (though often implicit) restrictions on the implementation of economic, social and cultural human rights, where the issues of reasonableness and legitimacy require particular attention, when the state of emergency in Ukraine is not announced. Dialectical, formal and legal, comparative and legal, system and structural, logical and semantic and other methods of scientific cognition have been used to solve the set tasks. Theoretical provisions and legal principles of introducing and realizing guarantees and restrictions of economic, social and cultural human rights (rights to health care, safe working conditions, business activity, equal access to public service, education, sufficient standard of living, social protection, etc.) have been analyzed. in terms of preventing the spread of COVID-19 in Ukraine. The nature and features of the established anti-epidemic measures have been characterized.It has been determined that the lawful introduction of a number of reasonable and proportional restrictions on the implementation of economic, social and cultural human rights within the framework of preventive and anti-epidemic measures to prevent the spread of COVID-19 in Ukraine is justified in general by the interests of effective protection against this infectious disease. It has been established that some of the significant restrictions on the implementation of these human rights in connection with the COVID-19 pandemic in Ukraine are unsystematic and have contradictory legal nature, are insufficiently justified and proportionate to anti-epidemic goals, demonstrate the features of discrimination, are insufficiently specified in content and implementation procedure, as well as are not provided with additional guarantees for the realization of these human rights.The author has grounded the ways for improving the guarantees and restrictions on the implementation of economic, social and cultural human rights in terms of preventing the spread of COVID-19 in Ukraine, which primarily require a comprehensive regulation of the relevant law and timely updating of their content and the implementation procedure, orientation of anti-epidemic measures not on restricting human rights, but on establishing special conditions of their realization with observance of the strengthened sanitary rules; ensuring the balance of the minimum necessary restrictions on human rights among themselves and with sufficient guarantees for their implementation.